1988
DOI: 10.1902/jop.1988.59.8.524
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of New Attachment Formation Using a Microfibhllar Collagen Barrier

Abstract: The objective of this study was to evaluate the effectiveness of microfibrillar collagen as a barrier to prevent epithelial migration and allow for guided tissue regeneration. Fourteen study teeth were selected. Mucoperiosteal flaps were elevated and roots were debrided and planed. Avitene was placed over teeth and alveolar bone. Flaps were then sutured over it. At control sites no Avitene was placed. At 90 days, block sections were obtained and processed for histologic and histometric evaluation. Results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…31,[42][43][44][45] The mean PD reduction from these studies ranged from 3.1 to 5.5 mm in collagen-treated groups, while only 2.2 to 2.8 mm reductions were noted in controls. However, Tanner et al 41 showed no difference in clinical attachment gain when comparing collagen membranes to flap debridement alone. It should be noted that this study was done in only 4 patients with hopeless teeth, and results were obtained only at 3 months.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…31,[42][43][44][45] The mean PD reduction from these studies ranged from 3.1 to 5.5 mm in collagen-treated groups, while only 2.2 to 2.8 mm reductions were noted in controls. However, Tanner et al 41 showed no difference in clinical attachment gain when comparing collagen membranes to flap debridement alone. It should be noted that this study was done in only 4 patients with hopeless teeth, and results were obtained only at 3 months.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Since the late 1980s, collagen membranes have been tested for their ability to promote regeneration in periodontal intrabony defects (Table 3). 31,[41][42][43][44][45][46] Most studies have shown significantly greater probing depth (PD) reduction, clinical attachment gain, and bone fill in collagen-treated groups than open debridement controls. 31,[42][43][44][45] The mean PD reduction from these studies ranged from 3.1 to 5.5 mm in collagen-treated groups, while only 2.2 to 2.8 mm reductions were noted in controls.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Da sich trotz op timaler Mundhygiene bei einigen PD Patienten kein dauerhafter Therapieer folg einstellte und sich sowohl die Ent zündungen als auch die Läsionen nicht mit der Menge an bakterieller Plaque er klären ließen, entwickelte sich die spezifische Plaquehypothese. Sie postuliert die qualitativen Plaqueveränderungen und das Überwuchern von parodontalpatho genen Keimen als Auslöser der entzünd lichen Reaktion [28].…”
Section: Chronische Parodontalerkrankungenunclassified
“…Avitene® is a microfibrillar hemostatic collagen Type-I membrane derived from bovine corium. Histological evaluation after a clinical study has shown that this membrane was not clinically effective and is difficult to handle during surgery [205]. Figure 5 illustrates some clinical applications of two absorbable collagen membranes (Fig.…”
Section: Barrier Membranes For Periodontal Guided Regeneration Applicmentioning
confidence: 99%